2018
DOI: 10.1093/ibd/izx054
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Vedolizumab in Preventing Postoperative Recurrence of Crohn’s Disease

Abstract: In the present retrospective cohort study of real-world experience, vedolizumab was shown to be commonly used as postoperative treatment for CD especially in high risk patients. Multivariate and propensity score-matched analyses showed that postoperative endoscopic recurrence in CD was higher with vedolizumab than with anti-TNF-α agents, but further investigation including controlled trials is required before determining the utility of vedolizumab in preventing postoperative recurrence of CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 23 publications
0
38
0
2
Order By: Relevance
“…Altogether 87 articles were selected for detailed evaluation, among which 24 articles were included (Figure 1). Generally, articles originated from Europe, 21‐36 Japan, 28,37‐41 the United States 42,43 and Oceania, 44 comprising 11 RCTs, 23,26,29,32,34,36,38,39,41,43,44 and 13 cohort or case‐control studies 21,22,24,25,27,28,30,31,33,35,37,40,42 . Most of the articles prescribed anti‐TNF‐α therapy, either with infliximab or adalimumab, with one article using vedolizumab.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Altogether 87 articles were selected for detailed evaluation, among which 24 articles were included (Figure 1). Generally, articles originated from Europe, 21‐36 Japan, 28,37‐41 the United States 42,43 and Oceania, 44 comprising 11 RCTs, 23,26,29,32,34,36,38,39,41,43,44 and 13 cohort or case‐control studies 21,22,24,25,27,28,30,31,33,35,37,40,42 . Most of the articles prescribed anti‐TNF‐α therapy, either with infliximab or adalimumab, with one article using vedolizumab.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 1042 participants were prescribed biologics as prophylaxis for the prevention of POR. Endoscopic recurrence was defined according to a Rutgeerts' score >i2, 5 and SES‐CD, 42 while the definition of clinical remission varied across studies. A summary of the included articles can be found in Table S1 and the results of quality assessment can be found in Table S2 and Figure S1.…”
Section: Resultsmentioning
confidence: 99%
“…71-19.4, p = 0.005). 67 However, there were a multitude of confounding factors and limitations to this analysis including key population differences. 68 There is limited data assessing the efficacy of vedolizumab in treating POR.…”
Section: Biologic Therapies For Postoperative CD Recurrencementioning
confidence: 99%
“…The effectiveness in preventing postoperative recurrence is unknown. In retrospective study of patients who underwent CD-related surgery, it was found that the rate of endoscopic remission at 6–12 months in the vedolizumab group was 25%, which was significantly lower than that in the anti-TNF group (66%, p = 0.01) [71]. Further prospective multicenter studies are urgently needed.…”
Section: Vedolizumab In Special Populationmentioning
confidence: 99%